Insecticide-Treated Nets Utilization and Associated Factors among under-5 Years Old Children in Mirab-Abaya District, Gamo-Gofa Zone, Ethiopia - Admasie, Amha; Zemba, Amanuel; Paulos, Wondimagegn (Frontiers in Public Health, 2018)
Background: Malaria can be prevented using cost-effective interventions. It can be prevented at large via the use of Insecticide-Treated Mosquito Nets (ITNs). The use of ITNs decreases malaria mortality rates by 55% in under-five years old children in Africa. Ethiopia, realizing the effectiveness, scaling up distribution and utilization of ITNs to cover 100% of children less than five years of age. However, little is known about ITNs utilization and factors associated with the utilization in under-five years old children in the study area yet. The purpose of this study was to assess the level and associated factors of ITNs utilization in under-five years old children among households with under-five years old children of Mirab Abaya District, Gamo Gofa Zone, Ethiopia. Methods: A community based cross-sectional study was conducted during August to September, 2016. Six study Kebeles were identified by simple random sampling technique and 398 households with at least one under-five years old children were selected by random sampling technique using computer generated random numbers from health post family folders. Structured, interviewer questionnaire was administered to mothers or care givers of the children. Data was entered to Epi Info Version 3.5 and analyzed in SPSS version 21 statistical software. Bivariate and multivariate logistic regression analysis was done. P value <0.05 and odds ratio with 95 % confidence interval were used for the determination of associations between dependent and predictor variables. Result: Among 398 under-five years old children assessed, the majority, 362(91.0%) of them had access to ITN, but only 137 (37.2%) of the child had ITNs utilization during the previous night prior to the survey. Households with age of mothers or care takers 31-44 years, AOR=0.03, 95% CI (0.01-0.07) and ≥45 years of age; AOR=0.05, 95% CI (0.01-0.58); households with family size ≤5 members, AOR=11.23, 95% CI (4.31-29.24); and households with sleeping space ≥2, AOR=13.59, 95% CI (4.40-41.93); were found to be significantly associated with under-five years old children ITNs utilization. Conclusion: Even though, a significant proportions of under-five years old children had access to ITN, only one-third of the participant child child were utilized it properly.